Hiding in plain sight : the invention of Donald Trump and the erosion of America - Kendzior, Sarah (Flatiron Books, 2020)
"From New York Times bestselling author Sarah Kendzior comes the bitingly honest examination of the calculated rise to power of Donald Trump since the 1980s and the erosion of American liberty. The story of Donald Trump's rise to power is the story of a buried American history - buried because people in power liked it that way. It was visible without being seen, influential without being named, ubiquitous without being overt. Sarah Kendzior's Hiding in Plain Sight pulls back the veil on a history spanning decades, a history of an American autocrat in the making. In doing so, she reveals the inherent fragility of American democracy - how our continual loss of freedom, the rise of consolidated corruption, and the secrets behind a burgeoning autocratic United States have been hiding in plain sight for decades. In Kendzior's signature and celebrated style, she expertly outlines Trump's meteoric rise from the 1980s until today, interlinking key moments of his life with the degradation of the American political system and the continual erosion of our civil liberties by foreign powers. Kendzior also offers a never-before-seen look at her lifelong tendency to be in the wrong place at the wrong time - living in New York through 9/11 and in St. Louis during the Ferguson uprising, and researching media and authoritarianism when Trump emerged using the same tactics as the post-Soviet dictatorships she had long studied. It is a terrible feeling to sense a threat coming, but it is worse when we let apathy, doubt, and fear prevent us from preparing ourselves. Hiding in Plain Sight confronts the injustice we have too long ignored because the truth is the only way forward"--